Tumor immune-vascular crosstalk: synergy and translation of immune checkpoint inhibitors and anti-angiogenic agents in melanoma - Xie, Yijie; Ho, I.; Liu, Zhipeng; Chen, Keyu; Zhou, Minjie; Ha, Guodong; Duan, Lincheng; Zhao, Zhengyu; Cai, Dingjun (Frontiers in Immunology, 2026)
Melanoma is the most aggressive form of skin cancer. Although immune checkpoint inhibitors (ICIs) have led to major therapeutic breakthroughs, monotherapy remains limited by suboptimal response rates and pronounced resistance. In recent years, combination strategies integrating ICIs with anti-angiogenic agents have demonstrated substantial synergistic antitumor potential. This review systematically summarizes the mechanisms underlying this synergy, including cross-regulation between immune checkpoints and angiogenic factors (such as VEGF and ANG-2), the remodeling of the tumor immune microenvironment by anti-angiogenic agents, and feedback regulation of angiogenesis by ICIs. Preclinical studies indicate that such combinations can induce vascular normalization and enhance T-cell infiltration, thereby reversing immunosuppression. Subsequently, multiple clinical studies have confirmed that, compared with ICI monotherapy, combination therapy provides superior efficacy and acceptable safety in patients with advanced, mucosal, acral, and even brain-metastatic melanoma. Although the combined approach may increase adverse events such as cardiovascular complications and dermatologic toxicity, these risks can be controlled through multidisciplinary management. Overall, ICI-based combination therapy with anti-angiogenic agents represents a promising therapeutic paradigm for melanoma. Future research should focus on biomarker discovery and optimization of individualized precision strategies to maximize patient survival benefits.